Long-term spatial and temporal trends, and source apportionment of polycyclic aromatic compounds in the Athabasca Oil Sands Region. (1st January 2021) - Chibwe, Leah; Muir, Derek C.G.; Gopalapillai, Yamini; Shang, Dayue; Kirk, Jane L.; Manzano, Carlos A.; Atkinson, Beau; Wang, Xiaowa; Teixeira, Camilla
Abstract: We investigated the spatio-temporal trends of polycyclic aromatic compounds (PACs) deposition in the Athabasca Oil Sands Region (AOSR) between 2008 and 2017, and applied source apportionment tools to assess sources using snowpacks. Estimated PAC mass deposition was significantly correlated with crude oil production (R 2 = 0.48, p = 0.03), and increased between 2008 and 2017. Loadings of alkylated PACs c1-, c2-fluorenes/pyrenes and c1-, c3-benzo[a]anthracenes/chrysenes/triphenylenes significantly increased at mid-field sites (25–50 km from central industrial reference site, AR6) (Mann-Kendall, p < 0.05) reflecting physical expansion of the AOSR. The distance from emission sources was important in the deposition of PACs, including the distance from AR6 (R 2 = 0.69–0.91), nearest petcoke storage (R 2 = 0.77–0.88), 0.89) and upgrader stack (R 2 = 0.56–0.61). Source apportionment PAC distribution profiles of the source materials (petcokes, oil sand ores, road dust) did not show unique matching profiles with the snowpacks. However, the minimal presence of retene in petcokes and an abundance of benzo[ghi]fluoranthene in road dust was observed, and suggests potential for these compounds as chemical markers in distinguishing sources. Furthermore, correlations between PACs and selected metal(loid)s in the AOSR snowpacks were assessed to infer potential common sources. Significant positive (p < 0.05) correlations between metal(loid)s enriched in bitumen (vanadium, molybdenum, nickel) and PACs, at near to mid-field (0–50 km from AR6) sites suggests common sources or similar transfer and fate processes. The results of our study convey data necessary for monitoring studies in the constantly developing AOSR, advance our knowledge of PACs profiles in source materials (including the much less studied alkylated PACs and dibenzothiophenes), which will be valuable for other studies related to oil pollution, urban run-off and forest fires. PACs mass deposition increasing between 2008 and 2017 coincident with crude oil production, and retene and benzo[ghi]fluoranthene show potential in distinguishing AOSR sources. Graphical abstract: Image 1 Highlights: Polycyclic aromatic compounds (PACs) mass deposition increases between 2008 and 2017. PACs mass deposition increase is coincident with crude oil production. Alkylated PACs and dibenzothiopenes fluxes are comparable to modelled estimates.